Pengaruh Media Video Terhadap Pengetahuan Tentang Radiasi Sinar-X di Instalasi Radiologi - Dewani Anggita Putri; Afriyanto; Nopia Wati; Riska Yanuarti (Public Health Department, Faculty of Health Science University Muhammadiyah Bengkulu, 2026)
Background: Radiology is a branch of medicine that examines or diagnoses the internal parts of the human body using imaging technology, including both electromagnetic and mechanical waves. Bhayangkara Hospital in Bengkulu has a radiology facility that utilizes X-ray radiation as a medical support facility. The equipment used includes conventional X-rays, CT scans, panoramic X-rays, mobile X-rays, and ultrasound. The purpose of this study was to determine the effect of video media on knowledge of X-ray radiation in the Radiology Installation at Bhayangkara Hospital in Bengkulu City. Methods: This study used a quantitative study with a quasi-experimental design. The research design was experimental. The sample size was 52 respondents. The results were analyzed using the Wilcoxon test. Results: The level of patient knowledge about X-ray radiation after receiving health education through video media increased compared to before the intervention. The Wilcoxon Signed Rank Test showed a Z-value of -5.894 with an Asymp. Sig. (2-tailed) value of 0.000. This significance value is less than α = 0.05. Suggestion: Bhayangkara Hospital, Bengkulu City, especially the Radiology Department, is expected to incorporate video-based health education into routine patient education. Keywords: Radiology, X-rays, Knowledge